Management of relapses after primary therapy for prostate cancer - Jassem, Jacek; Zaucha, Renata (Contemporary Oncology/Współczesna Onkologia, 2003)
The widespread use of screening procedures including routine testing of serum prostate specific antigen (PSA) resulted in the increased diagnosis of early prostate cancer. Rising PSA is the most frequent sign of failure after definitive local treatment. The clinical stage of prostate cancer, Gleason score and PSA level have been included in mathematical models developed to predict the risk of biochemical failure. Defining which patient groups benefit from salvage local therapy is crucial for the success of treatment. Therefore, examinations like bone scan or computed tomography of the pelvis and abdomen are performed to establish whether the relapse is organ confined or disseminated. Unfortunately, all contemporary diagnostic tools are of limited value, especially in cases with PSA levels below 30 ng/ml. Therefore, to increase the chance of relapse detection, the dynamics of PSA rise, measured by PSA level doubling time, are being included in the work-up. There is no widely accepted therapeutic strategy in terms of timing and type of treatment in cases of biochemical failure. Salvage radical prostatectomy or cryotherapy are offered in local relapses after radical radiotherapy, whereas failures after primary surgery are managed with radical radiotherapy. The time to biochemical failure, PSA level and the PSA doubling time are the most important prognostic factors. The relapse-free five-year survival after salvage therapy varies between 10 and 50%.